A gamificação no ensino de biologia: uma proposta didático pedagógica no Centro Educa Mais Maria Mônica Vale - TEIXEIRA, Aglaenne Reis Lima (2024)
This work aimed to investigate gamification in biology education with the perspective of creating a pedagogical guideline notebook for gamification in biology education to contribute to pedagogical practice in the context of high school. As a theoretical basis, the assumptions of Kapp (2012), Blair and Mesch (2014), Martins and Giraffa (2018), and Krasilchik (2019) were used. The chosen methodological strategy was applied qualitative research, specifically a case study, with the research site being the Educa Mais Maria Mônica Valle Center and the participation of three biology teachers who teach in the three grades of high school. To analyze the collected data, Bardin's content analysis (2021) was used. Therefore, data collection started with the observation of the research site, followed by the application of a diagnostic questionnaire to the participants. As a result, we observed that the research site has a physical and operational structure that is considered privileged and serves a large audience of students. Furthermore, it was observed that the participants use the internet and books as sources of research, have previously used games as a teaching tool, and associate the use of games with entertainment and motivation. Additionally, the topic of botany was highlighted as needing alternative methods for better student understanding. Based on this information, we held a workshop on gamified practices for teaching biology, which allowed us to discuss the main concepts and develop and implement gamified lessons in some high school classes. Afterward, we conducted a semi-structured interview with the participating teachers in which they positively evaluated the gamification methodology, noting the students' engagement during the gamified classes. However, they expressed difficulties in applying gamification, such as limited time for planning, and the school's physical and material infrastructure. In this way, it was found that the present study contributed to Biology teaching in this educational center by helping teachers rethink new teaching practices through the gamification methodology. Based on this, a pedagogical guidebook was developed, containing both theoretical and methodological content, which will serve as auxiliary material for the development of pedagogical practices for other teachers.